2020
DOI: 10.1021/acsaem.0c01587
|View full text |Cite
|
Sign up to set email alerts
|

Significant Photostability Enhancement of Inverted Organic Solar Cells by Inserting an N-Annulated Perylene Diimide (PDIN-H) between the ZnO Electron Extraction Layer and the Organic Active Layer

Abstract: We investigate the effect of adding an N-annulated perylene diimide dye with a pyrrolic NH functional group (PDIN-H) onto an electron extraction layer (EEL) in a bilayer configuration (ZnO/PDIN-H) on the photostability of inverted organic solar cells (OSCs). To do so, we insert a thin layer of PDIN-H in between the ZnO layer and the bulk heterojunction (BHJ) active layer. Results show that under prolonged ultraviolet (UV) irradiation, the cells with the ZnO/PDIN-H EEL exhibit substantially higher photostabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…In a previous work, [25] we showed that UV irradiation does not appreciably alter the morphology or the UV-vis absorption www.advsustainsys.com characteristics of P3HT:PC60BM films coated on ZnO, indicating that morphological changes or photocatalytic effects [40] are not primary root causes in the observed low photostability of P3HT:PC60BM-based OSCs with ZnO EEL. Knowing from the literature that low morphological stability might be a factor in case of non-fullerene-based devices, [41] we conducted atomic force microscopy (AFM) and UV-vis measurements on the PM6:Y6 films.…”
Section: Wwwadvsustainsyscommentioning
confidence: 70%
See 2 more Smart Citations
“…In a previous work, [25] we showed that UV irradiation does not appreciably alter the morphology or the UV-vis absorption www.advsustainsys.com characteristics of P3HT:PC60BM films coated on ZnO, indicating that morphological changes or photocatalytic effects [40] are not primary root causes in the observed low photostability of P3HT:PC60BM-based OSCs with ZnO EEL. Knowing from the literature that low morphological stability might be a factor in case of non-fullerene-based devices, [41] we conducted atomic force microscopy (AFM) and UV-vis measurements on the PM6:Y6 films.…”
Section: Wwwadvsustainsyscommentioning
confidence: 70%
“…The results of the ZnO cells are consistent with our recent findings that increased surface recombination is the primary cause of degradation in P3HT:PC60BM-based cells with ZnO under prolonged irradiation. [25] The observations also show that the higher photostability of the cells with DM-EELs originates primarily from an unchanged recombination mechanism in these cells. Since, apart from the EELs, all devices are structurally identical, differences in recombination mechanisms among them after the UV-irradiation must be associated with the electron collection contacts.…”
Section: Wwwadvsustainsyscommentioning
confidence: 75%
See 1 more Smart Citation
“…Chemical structures of the BHJ photoactive materials a) PTQ10, Y6, and electron transport layer modifiers b) PDIN‐Boc, and PDIN‐H. c) Energy level diagram of the materials used (ITO, [ 19 ] SnO 2 [ 19 ] , PDIN‐H, [ 21 ] Y6, [ 19 ] PTQ10, [ 23 ] MoO x , [ 19 ] Ag [ 24 ] ) in the OPV device. d) Schematic diagram of the champion OPV device structure identified.…”
Section: Resultsmentioning
confidence: 99%
“…[ 16–19 ] Our team has recently demonstrated that an N‐annulated PDI with a functional N‐H bond (PDIN‐H) can be solution processed onto ZnO, decreasing the surface hydrophobicity and lowering the work function, leading to improvements in both OPV device PCE and stability. [ 20–22 ]…”
Section: Introductionmentioning
confidence: 99%